DAMPAK ZAKAT DAN TANGGUNG JAWAB SOSIAL (CSR) PADA REPUTASI DAN HASIL KERJA BANK UMUM SYARIAH - Nuril Alfi Darsiya; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe aims of this study to determine the effect of zakat and Corporate Social Responsibility on the reputation and performance of Islamic Commercial Banks. This analysis uses independent variables namely zakat and CSR. The dependent variable is the reputation and performance of sharia commercial banks. The samples in this study were Islamic public banks registered at Bank Indonesia (BI) and the Indonesia Stock Exchange (IDX) in 2014-2017. Sample selection is done by purposive sampling method. The technical data analysis used is the logistic regression test. The results of the study show that: (1) zakat and CSR have a significant influence on the reputation of Islamic commercial banks. (2) Zakat has a positive but not significant relationship to the reputation of Islamic commercial banks. (3) CSR has a significant influence on the reputation of Islamic commercial banks. (4) zakat and CSR have a significant influence on the performance of sharia commercial banks. (5) zakat has a positive but not significant relationship to the performance of Islamic commercial banks. (6) CSR has a positive but not significant relationship to the performance of Islamic commercial banks.Keywords: zakat, corporate social responsibility, reputation, performance